Eficiência de utilização de nitrogênio e potássio pelo melão pele de sapo fertirrigado em diferentes lâminas de irrigação - Temóteo, Amansleone da Silva (Universidade Federal Rural do Semi-Árido, 2006)
This work had as objective, to evaluate the efficiency nutrient utilization in development stages of the Frog as a function skin melon of N and K dosage applied through fertirrigation different depths of irrigation. Three experiments were installed simultaneously in the same area, in the Norfruit Farm, located in the county of Mossoró - RN, in the period of September to December of 2004. Each experiment consisted of a depth of different irrigation,defined as a function of the total of irrigation demand - where (NTI), being L1 = 0,7.NTI, L2= 0,9.NTI and L3 = 1,1.NTI corresponding to 281, 349 and 423 mm respectively. The experimental delineation used was a block-type randomized in factorial arrangement of 3 x 3 + 2. The eleven treatments of the factorial design consisted of the combination of three dosages of N (N1, N2 and N3) and three dosages of K (K1, K2 and K3) and two added treatments (N0K2 and N2K0), corresponding to the following dosages N0 = 0, N1 = 91, N2 =140 and N3 = 184 kg ha-1 of N and K0 = 0, K1 = 174, K2= 260 and K3 = 346 kg ha-1 of K2O. The total and marketable yield was evaluated and dried, biomass, N and K content in the plant and in the soil, the content and absorption rate of N and K, nutritional balance and efficiency of N and K. Use dosages of applied N and K, above those used by the producers of the region(140 kg ha-1 of N and 260 kg ha-1 of K) did not promote increases in the production, in the accumulation total dried of biomass, and reduced the efficiency of use of N and K nutrients. The of depth irrigation of 349 mm was enough to get the maximum marketable yield (31,16 Mg ha-1). The effect of the concentration with the doses of N and K applied in the plant occurred after 49 days after sowing. The biggest of rate N absorption was between 46 and 52 of days after planting and for K, between 52 and 63 DAP. With the dosages N1K1, N2K2 and L2 derth showing the highest absorptions. The efficiency of use of K for the cantaloup crop was greater that of the N, and was smaller with the highest dosage of the nutrients
Nitrogen and potassium use efficiency by Fertirrigated frog skin melon under different irrigation depths
Keywords: Cucumis melo; Mineral nutrition; Fertirrigation; Cucumis melo; Nutrição mineral; Fertirrigação; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA